221k views
4 votes
Solve for b. −16b=3 What is the answer? a. −18 b. −2 c. 2 d. 18

User Ken Block
by
4.7k points

2 Answers

3 votes


\text{If is}\ -(1)/(6)b\ \text{then}\\\\-(1)/(6)b=3\qquad\text{multiply both sides by (-6)}\\\\(-6\!\!\!\!\!\diagup^1)\cdot\left(-(1)/(\\ot6_1)b\right)=3(-6)\\\\(-1)(-b)=-18\\\\\boxed{b=-18}\to\boxed{a.}\\\\\text{If is}\ -16b,\ \text{then}\\\\-16b=3\qquad\text{divide both sides by (-16)}\\\\b=(3)/(-16)\\\\\boxed{b=-(1)/(16)}

User Cliffordheath
by
5.7k points
6 votes

Answer:

a. −18

Explanation:

-1/6 b =3

Multiply by -6 on each side

-6 * -1/6 b = 3*-6

b = -18

User Evanne
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.